(untitled) (Eurasian Research Bulletin, 2023)
The article presents data on the clinical and immunological features of modern juvenile rheumatoid arthritis and methods of its therapy. One of the urgent problems of modern rheumatology is chronic inflammatory diseases of the joints in children, united under the general term "juvenile arthritis" or, in accordance with the international classification of 2017 - "juvenile idiopathic arthritis". In domestic rheumatology, the term "juvenile rheumatoid arthritis" (JRA) is widely used. The etiology and pathogenesis of JRA are still unknown.This disease is characterized by pronounced clinical polymorphism and genetic heterogeneity, in connection with which it combines independent inflammatory diseases of the joints in children, different in course and prognosis, and possibly having certain equivalents in adults.